Development of Rational Function Integral E-Worksheet with Linear Factor Denominators to Improve Mathematical Creative Thinking Ability - Solfitri, Titi; Siregar, Hesty Marwani; Syofni; Anggraini, Rini Dian; Apristi, Ivo (LPPM Undiksha, 2023)
There is no electronic worksheet that can help students to optimize their mathematical creative thinking skills in the Integral Integration technique of rational functions with the denominator is a linear factor being the background for this research. This research aims to produce an e-worksheet that can be used in integral calculus courses, especially material for Integral Integration techniques of rational functions with the denominators being linear factors, and can improve the ability to think creatively mathematically. The research was conducted using the ADDIE development model. The research subjects were 15 students of Mathematics Education at the University of Riau. Data collection instruments used questionnaires and tests with quantitative and qualitative descriptive analysis. From the calculation of the validation score, overall, the e-worksheet is valid and can be used by Mathematics Education students in Integral Calculus courses. Based on the results of the second student response questionnaire, the e-worksheet met the practical criteria with the achievement of e-worksheet 1 of 83.33% and e-worksheet 2 of 76.3%. From the results of the worksheet effectiveness test, there has been an increase in students' mathematical creative thinking ability after using e-worksheet from 2.73 to 7.6 and is in the medium category. Referring to the results of this study means that the developed e-worksheet is feasible to use and can improve students' mathematical creative thinking abilities.